2003
DOI: 10.3354/meps265289
|View full text |Cite
|
Sign up to set email alerts
|

Internal bioerosion by macroborers in Pocillopora spp. in the tropical eastern Pacific

Abstract: Bioerosion of branched corals was assessed in a fringing reef (Playa Blanca) and a patch reef (Gorgonilla) of Gorgona Island in the tropical eastern Pacific. Cylinder-shaped experimental units (EUs), made from branches of Pocillopora spp., were set 50 cm above the sea bottom for 6, 12 and 18 mo in Playa Blanca (4 zones: Back Reef, Reef-Flat Crest, Reef Front and Reef Slope) and the Gorgonilla patch reef. Borers were represented by bivalves Lithophaga spp. and Gastrochaena ovata, polychaetes, sipunculids and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
23
0
4
Order By: Relevance
“…Perry (1998) demonstrated that bioerosion rates in dead coral substrata also increased from 5 to 30 m depth, and suggested that this increase might be due to a depth-dependent decline in calcification rates and skeletal densities (Bosscher 1993). However, other studies did not find any correlation between depth and internal macrobioerosion intensity Londoño-Cruz et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Perry (1998) demonstrated that bioerosion rates in dead coral substrata also increased from 5 to 30 m depth, and suggested that this increase might be due to a depth-dependent decline in calcification rates and skeletal densities (Bosscher 1993). However, other studies did not find any correlation between depth and internal macrobioerosion intensity Londoño-Cruz et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Although strongly related to turbidity, chlorophyll a and depth, internal macrobioeroder densities in massive Porites are also affected by a number of other biotic and abiotic factors Perry 1998;Londoño-Cruz et al 2003). For instance, sedimentation may affect the abundance of some bioeroders by blanketing the habitat available for settlement , and strong water currents are also related to high abundances of some filter feeders such as lithophagids Londoño-Cruz et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological erosion (bioerosion) as a general term refers to the destruction and removal of consolidated minerals of lithic substrate by the direct action of organisms (Neumann, 1966). The most common agents of bioerosion are fish (Risk and Sammarco, 1982), sea urchins (Mokady et al, 1996), algae (Kobluk and Risk, 1977), molluscs (Londono-Cruz et al, 2003;Hutchings et al, 2005), polychaetes and sipunculids (LondonoCruz et al, 2003) and sponges Hutchings et al, 2005). Physical erosion is caused by wave movement, storms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…PRIMER v6 (Plymouth Marine Laboratory, Clarke and Warwick, 2001) was used for analysis of community. Cochran tests were used to test for homogeneity of variances before ANOVA.…”
Section: Statistical Analysesmentioning
confidence: 99%